Pengaruh Produk Domestik Regional Bruto (PDRB), Pengangguran dan Kemiskinan terhadap Islamic Human Development Index (I-HDI) 38 Provinsi di Indonesia 2023-2025 - Mardyan Nugraha; Anton Bawono; Rina Rosia (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP), unemployment rate, and poverty on the Islamic Human Development Index (I-HDI) across 38 provinces in Indonesia during the 2023–2025 period. Secondary data were sourced from Statistics Indonesia (BPS) and analyzed using panel data regression with the Fixed Effect Model (FEM) approach. The results indicate that simultaneously, the three independent variables significantly affect I-HDI with an R2 value of 93.66%. Partially, GRDP and unemployment have a positive and significant impact on I-HDI. The positive coefficient of unemployment presumably represents the characteristics of developed regions with a concentration of educated unemployment who maintain high human capital. Meanwhile, the poverty rate has no significant effect on I-HDI. This insignificance indicates the resilience of Islamic human development against material shocks, which potentially driven by the existence of informal social safety nets from Islamic philanthropic instruments (ZISWAF). This study recommends strengthening inclusive economic policies targeting human capital quality and optimizing the integration of socio-religious instruments.